Gender Inequalities and Language Expression in Education - Nuraida, I; Nasir, M (KnE Social Sciences, 2018)
The aim of this research is to investigate whether the difficulties found by men and women in using a language are just caused by their sexual differences. It has been shown that the factor of language expression is more important and determines how men and women should speak. There are a number of factors that influence the differences in language expression, i.e. domination or power, the different ways of treating men and women, and socialization. Because of these factors, we find some expressions in the English language that represent gender inequalities, e.g. asymmetric marked and unmarked terms, and semantic derogation. Keywords: education, gender, language expression